Increased expression of Filaggrin and Claudin‐1 in the ocular surface of patients with atopic dermatitis. (9th November 2021) - Callou, T.M.P.; Orfali, R.L.; Sotto, M.N.; Pereira, N.V.; Zaniboni, M.C.; Aoki, V.; Brito, M.P.; Matsuda, M.; Santo, R.M.
Abstract: Background: Atopic dermatitis (AD) is an itchy, chronic and inflammatory skin condition, with dysfunctional immune response and skin barrier defects. Reduction of filaggrin (FLG) and tight junctions (TJ) proteins, such as claudin‐1 (CLDN‐1), expression in cutaneous epithelial barrier is remarkable in AD pathogenesis. Ocular involvement occurs in approximately 40% of AD patients leading to changes in the structure of the conjunctiva. Objectives: We aimed to evaluate the expression of FLG and CLDN‐1 in the ocular surface of adults with AD, analysing bulbar conjunctival cells collected by a novel non‐invasive cellular imprint. Methods: Bulbar conjunctival epithelial cells were collected by cellular imprint technique, and FLG and CLDN‐1 expression were assessed by immunofluorescence (IF) and real‐time polymerase chain reaction (RT‐PCR). Results: We detected increased expression of FLG and CLDN‐1, as well as their transcript levels in AD patients compared with healthy controls (HC). There was a positive correlation between tear film break‐up time (TBUT) and FLG expression. Fluorescein staining was inversely associated with FLG expression. Conclusions: Our results may reflect a reactive response of the ocular surface to AD‐related ocular inflammation and associated dry eye disease. Further investigations focusing on the role of FLG and TJ expression in the ocular surface of AD patients may increment the understanding of the pathophysiology of extracutaneous AD and developing future targeted therapies.